A flying start? Maternity leave benefits and long run outcomes of children - Pedro Carneiro; Katrine V. Loken; Kjell G. Salvanes (Institute for the Study of Labor (IZA), 2011)
We study the impact on children of increasing maternity leave benefits using a reform that increased paid and unpaid maternity leave in Norway in July 1977. Mothers giving birth before this date were eligible only for 12 weeks of unpaid leave, while those giving birth after were entitled to 4 months of paid leave and 12 months of unpaid leave. This increased time with the child led to a 2.7 percentage points decline in high school dropout and a 5% increase in wages at age 30. For mothers with low education we find a 5.2 percentage points decline in high school dropout and an 8% increase in wages at age 30. The effect is especially large for children of those mothers who, prior to the reform, would take very low levels of unpaid leave.
urn:nbn:de:101:1-201106224748
Keywords: J13; J18; 330; maternity leave; children's outcomes